PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK YANG TERDAFTAR DI KANTOR PELAYANAN PAJAK PRATAMA SAMARINDA - JERI PALI; ISKANDAR -; BRAMANTIKA OKTAVIANTI (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
Curerent tax is a source of revenues for the country. Lack of tax compliance becomes a problem in maximizing tax revenue. In this study the authors conducted a study of corporate taxpayers who have been using the system on-line in reporting their income taxes at the tax office Pratama Samarinda. This research uses primary data obtained from questionnaires media. Population in this study is the taxpayer who had never reported the income tax system with on-line. The number of samples is determined as many as 40 people. By using partial least square analysis of the data showed that the organizational structure and significant positive effect on tax compliance while organizational procedures, organizational strategy and organizational culture negative effect on tax compliance.Keyword: Tax Complience, Organizational Structure, Organizational Procedures, Organizational Strategy, Organizatioanal Culture.